1996
DOI: 10.1007/bfb0102331
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and directing metabolite flux: Application to amino acid overproduction

Abstract: targets of the L-lysine and L-isoleucine biosynthesis of Corynebacterium glutamicum, high amino acid overproduction can be obtained with this bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 136 publications
(127 reference statements)
0
15
0
1
Order By: Relevance
“…However, the recent development of metabolic engineering tools, allowing the rational design of microorganisms for metabolite production (27), prompted us to evaluate an alternative process for trehalose overproduction in the gram-positive bacterium Corynebacterium glutamicum (23). C. glutamicum was chosen for three major reasons: (i) it produces, and excretes, trehalose (15); (ii) it has a metabolic control architecture simpler than that of other microorganisms, maybe as a result of its comparatively small 3,500-kb genome size (10); and (iii) it is widely used in industrial biotechnological processes (10).…”
mentioning
confidence: 99%
“…However, the recent development of metabolic engineering tools, allowing the rational design of microorganisms for metabolite production (27), prompted us to evaluate an alternative process for trehalose overproduction in the gram-positive bacterium Corynebacterium glutamicum (23). C. glutamicum was chosen for three major reasons: (i) it produces, and excretes, trehalose (15); (ii) it has a metabolic control architecture simpler than that of other microorganisms, maybe as a result of its comparatively small 3,500-kb genome size (10); and (iii) it is widely used in industrial biotechnological processes (10).…”
mentioning
confidence: 99%
“…It is also the most widely used microorganism for the industrial synthesis of amino acids (5). Although the physiological response of C. glutamicum to increases in osmotic pressure has been studied extensively, research has concentrated on individual pathways and not the organism's systemic response (7,9,10).…”
mentioning
confidence: 99%
“…Flux is the focal point of metabolic engineering. Different means of analyzing flux are (1) kinetic based models, (2) control theories, (3) tracer experiments, (4) magnetization transfer, (5) metabolite balancing, (6) enzyme analysis, and (7) genetic analysis [22]. Metabolic control analysis revealed that the overall flux through a metabolic pathway depends on several steps, not just a single rate-limiting reaction [31].…”
Section: Process Development In the Pilot Plant And Factorymentioning
confidence: 99%